Artificial Reproductive Technology Use and Family-Building Experiences of Female Adult Childhood Cancer Survivors: A Qualitative Study - Selena Banser; A. Fuchsia Howard; Sally Thorne; Karen J. Goddard (Current Oncology)
Purpose: Cancer treatments can result in subfertility or infertility in female adult childhood cancer survivors (ACCSs). While ACCSs may utilize assisted reproductive technology (ART) or other family-building options, the limited evidence describing their experiences remains a hindrance to developing and implementing appropriate patient-centered supports. The study’s aim is to describe the challenges female ACCSs experienced while navigating ART and family-building options, to inform improvements in clinical practice in a western Canadian province. Methods: In this qualitative Interpretive Description study, interviews were conducted with 15 female ACCSs and data were analyzed using an interpretive thematic approach and constant comparative techniques. Results: ACCSs’ narratives suggest they experienced five prominent challenges while navigating ART and family-building options, including (1) confronting unexpected, impaired fertility, (2) grieving loss and redefining identity, (3) encountering unsupportive healthcare, (4) exploring alternative paths of adoption and international family-building, and (5) facing financial strain. Conclusions: This exploratory study provides initial insights into the significant and multifaceted challenges female ACCSs experience related to family building and highlights gaps in healthcare services. Further research is warranted to articulate these challenges across contexts and the development and implementation of mitigating approaches. Implications for Cancer Survivors: The integration of comprehensive informational, psychosocial, and financial supports into existing cancer survivor and family-building services is vital to meeting female ACCSs’ unmet needs.